Severe Symptomatic Hypocalcemia from HIV Related Hypoparathyroidism - Sartaj Sandhu; Akshata Desai; Manav Batra; Robin Girdhar; Kaushik Chatterjee; E. Helen Kemp; Antoine Makdissi; Ajay Chaudhuri (Case Reports in Endocrinology)
We report the case of a 54-year-old Caucasian female who presented with a two-year history of persistent hypocalcemia requiring multiple hospitalizations. Her medical history was significant for HIV diagnosed four years ago. She denied any history of prior neck surgery or radiation. Her vital signs were stable with an unremarkable physical exam. Pertinent medications included calcium carbonate, vitamin D3, calcitriol, efavirenz, emtricitabine, tenofovir disoproxil, hydrochlorothiazide, and inhaled budesonide/formoterol. Laboratory testing showed total calcium of 5.7 mg/dL (normal range: 8.4-10.2 mg/dL), ionized calcium of 2.7 mg/dL (normal range: 4.5-5.5 mg/dL), serum phosphate of 6.3 mg/dL (normal range: 2.7-4.5 mg/dL), and intact PTH of 7.6 pg/mL (normal range: 15-65 pg/mL). She was diagnosed with primary hypoparathyroidism. Anti-calcium-sensing receptor antibodies and NALP5 antibodies were tested and found to be negative. During subsequent clinic visits, doses of calcium supplements and calcitriol were titrated. Last corrected serum calcium level was 9.18 mg/dL. She was subsequently lost to follow-up. This case gives insight into severe symptomatic hypocalcemia from primary hypoparathyroidism attributed to HIV infection. We suggest that calcium levels should be closely monitored in patients with HIV infection.